Avaliação da qualidade da prestação de serviços em um posto de saúde do município de Barcarena - NONATO, Rivanildo Farias (2021)
This research has as goal to develop an evaluation about the satisfaction with provision of services in a little hospital from the city of Barcarena, through comparative analysis of attendance quality from the point of view of the internal and external environment. The data obtained through the application of online forms, after being used and analyzes with helping of Microsoft Excel software, it made it possible to develop a spreadsheet that printened the average index with the highest dissatisfaction according to the services provided, so it was permissible to indicate the main measures that must be adapted to the service provided that reach the desired quality. In these contexts, improvement proposals were develop using the 5W1H toll, changing measures that could perform in systematic management on this little hospital.